The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1051/0004-6361/201526830
|View full text |Cite
|
Sign up to set email alerts
|

Search for HOOH in Orion

Abstract: Context. The abundance of key molecules determines the level of cooling that is necessary for the formation of stars and planetary systems. In this context, one needs to understand the details of the time dependent oxygen chemistry, leading to the formation of O 2 and H 2 O. Aims. We aim to determine the degree of correlation between the occurrence of O 2 and HOOH (hydrogen peroxide) in star-forming molecular clouds. We first detected O 2 and HOOH in ρ Oph A, we now search for HOOH in Orion OMC A, where O 2 ha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 19 publications
1
33
0
Order By: Relevance
“…The derived dust opacity curve has been computed for a particular volume density of the gas, n d (H) and this ought to be consistent with that 13 For ρ Oph A, the (anisotropic) radiation field is more intense by two orders of magnitude (Liseau et al 1999). …”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…The derived dust opacity curve has been computed for a particular volume density of the gas, n d (H) and this ought to be consistent with that 13 For ρ Oph A, the (anisotropic) radiation field is more intense by two orders of magnitude (Liseau et al 1999). …”
Section: Discussionsupporting
confidence: 60%
“…west and east of the dense core, with respective radii of 0.06 pc and 0.5 pc. The bright B2 star HD 147889 is situated more than half a parsec away to the southwest and behind the cloud (Liseau et al 1999). Together, these stellar radiation sources are heating the dust of ρ Oph A from the outside.…”
Section: Extended Dust Emissionmentioning
confidence: 99%
See 1 more Smart Citation
“…In two recent papers (Feng et al 2015;Liseau & Larsson 2015) a tentative detection of three species has been reported. We do not confirm these detections, as discussed below.…”
Section: Non-confirmation Of Species In Orionmentioning
confidence: 99%
“…The widespread distribution of Denriched formaldehyde and the detection of H 2 O 2 in ρ Oph A (Bergman et al 2011a,b) both support the idea that the O 2 could be present following the evaporation of ice mantles from dust grains. A search for H 2 O 2 in Orion was unsuccessful (Liseau & Larsson 2015) although the upper limits for hydrogen peroxide in interstellar ices, H 2 O 2 /H 2 O< 9%, do not rule out it being quite abundant on dust grains (Smith et al 2011). In Orion, the O 2 emission is confined to the H 2 Peak 1 position and the originally reported abundance ratio was O 2 /H 2 ∼ 10 −6 (Goldsmith et al 2011b).…”
Section: Discussionmentioning
confidence: 99%